PENGARUH TERPAAN IKLAN PINJAMAN ONLINE DI YOUTUBE, KUALITAS PESAN IKLAN, DAN DAYA TARIK IKLAN TERHADAP MINAT MENGAJUKAN PINJAMAN ONLINE PADA GENERASI Z - Shananda Alvita Arrivia; Yanuar Luqman (Interaksi Online, 2026)
The development of online loan advertisements on digital platforms makes the background in this study, especially YouTube which increasingly reaches the younger generation, namely Generation Z as active internet users. The interest in applying for online loans in Generation Z is allegedly influenced by the high intensity of advertising exposure, the quality of advertising messages, and the attractiveness of advertisements. This study aims to analyze the influence of online loan advertising exposure on YouTube, the quality of advertising messages, and the attractiveness of advertisements on interest in applying for online loans in Generation Z. This study uses a quantitative method with a survey approach. Data was obtained through the distribution of questionnaires to respondents with Generation Z criteria who had seen online loan ads on YouTube. To analyze the relationship between independent variables with bounds using multiple linear regression analysis. Based on the results of the study, between exposure to online loan ads on YouTube, the quality of the ad message, and the attractiveness of the advertisement have a positive and significant effect on the interest in applying for online loans in Generation Z, both simultaneously and partially. The regression coefficient value of the variable exposure to advertising is 0.445 with a significance level of 0.000, the quality of the ad message is 0.441 with a significance level of 0.000, and the attractiveness of the advertisement is 0.391 with a significance level of 0.000. In addition, the R Square value of 0.821 represents the three independent variables that are able to show an influence on the interest in applying for an online loan by 82.1%, while the remaining 17.9% is influenced by other variables outside the study. These findings show that the higher the intensity of ad exposure, the better the quality of the ad message, and the more attractive the ads displayed on YouTube, the higher the interest of Generation Z in applying for online loans.